Multi-decade catches of manta rays (Mobula alfredi, M. birostris) from South Africa reveal significant decline - Carpenter, Michelle; Parker, Denham; Dicken, Matthew L.; Griffiths, Charles L. (Frontiers in Marine Science, 2023)
Little is known about manta rays (Mobula alfredi and M. birsotris) in South Africa. This study analyzed a 41-year dataset from the KwaZulu-Natal bather protection program, which is the longest currently known catch dataset on manta rays. We investigated catch per unit effort and size composition of catches between 1981-2021 and used Generalized Additive Models and probability of encounter to analyze annual and seasonal trends and the effects of moon phase and location on catch rates. A significant decline in overall catches was observed, beginning in the late 1990s (p < 0.0001). The area between Anstey’s Beach in the north and Mtwalume in the south had the highest catches, which peaked in the late 1990s, after which there was a steady decline with only two or less catches in the area post 2015. Annually, catches increased in summer, suggesting that South African waters provide important habitat in manta rays seasonal distribution across the southern African coastline. Moon phase also had an effect on manta ray presence, with significantly more catches during spring tides at new and full moon. Many of the catches included juveniles, whereby a total of 841 individuals (52% of total catch) of confirmed juvenile size class (1400-2500 mm disc width) were caught. A greater proportion (70%) of juveniles were caught in the southernmost sampled area, from Hibberdene in the north to Mzamba in the south. The significant decline and spatial-temporal patterns found in this study have considerable implications for management.